Peran Petugas Kesehatan dalam Pencegahan dan Penanganan Stunting di Kabupaten Kolaka - Muhdar Muhdar; Rosmiati Rosmiati; Grace Tedy Tulak; Ekawati Saputri; Risqi Wahyu Susanti (Jurnal Kesehatan Andalas, 2022)
The nutritional problem in toddlers today is stunting which can be prevented by various actions that can be taken by health workers. Objectives: To described the role of health workers in all puskesmas in Kolaka Regency in an effort to prevent stunting.Methods: The design of this study was a descriptive survey by providing closed and open question questionnaires. The population was all health workers serving under-five nutrition spread across 14 health centers in Kolaka Regency. The research sample was determined by purposive sampling so that the number of samples was 30. Results: This study showed that 66.7% of health workers had not attended training, 60% were planning to innovate, but only 33.3% are innovating, and 93.3% are cooperating. The innovations that have been made include forming a nutrition-aware family team and a nutrition-smart mother class, while the obstacles experienced are the lack of public knowledge about stunting, the difficulty of changing people's behavior about the importance of nutrition, the lack of accurate tools in measuring children under five, and the lack of health workers who provide services. Conclusion: The role of health workers in preventing stunting in Kolaka Regency is quite good if it is supported by stunting prevention training and supporting tools so it is recommended that adequate training and tools are needed to prevent stunting.Keywords:  health workers, toddler nutrition, stunting